A case report of the clinical effect of chronic total occlusion recanalization on the instantaneous wave-free ratio in the donor artery. Issue 2 (21st March 2018) - Ahmad, Yousif; Al-Lamee, Rasha; Davies, Justin; Sen, Sayan
Abstract: Introduction: Coronary physiology is recommended for guiding percutaneous coronary intervention (PCI). Previous cases have demonstrated changes in fractional flow reserve in a donor collateral vessel after PCI to a chronic total occlusion (CTO). The behaviour of instantaneous wave-free ratio (iFR) in the context of CTO has not been described. Case presentation: In this case, we share the first case of the effect of CTO recanalization on iFR in the donor artery, and show how iFR can reflect the amount of myocardium subtended by a stenosis. Discussion: Instantaneous wave-free ratio is able to incorporate the amount of subtended myocardium in its quantification of coronary stenosis severity.